Analisis Kapasitas Saluran Drainase Untuk Mengurangi Genangan Air Di Kawasan Jalan Taduan Kecamatan Medan Tembung - Cinta Fhidelia Simanjuntak; Beatrix Denada Sidabukke; Rizky Simanjuntak (CV. SINAR HOWUHOWU, 2026)
Urban drainage systems play an important role in channeling rainwater and household wastewater so that they do not cause puddles or flooding in residential areas. Along with the increasing development and land use in urban areas, the capacity of drainage channels is often unable to accommodate the existing water discharge. This study aims to analyze the capacity of drainage channels located on Taduan Street, Medan Tembung District, and to determine their suitability for the existing rainfall discharge. The research method used is a quantitative method with data collection through field surveys to measure the dimensions of the drainage channels and collect rainfall data. The data were then analyzed to calculate the rainfall discharge and the capacity of the existing drainage channels. The results show that several parts of the channels experience sedimentation, narrowing, and the presence of household waste that obstructs water flow. These conditions reduce the capacity of the channels so that they are unable to accommodate water discharge optimally. Therefore, routine maintenance and improvement of channel dimensions are needed so that the drainage system can function more effectively in reducing water inundation.